1995
DOI: 10.1002/path.1711750406
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the tumour suppressor gene p53 is not implicated in neuroendocrine tumour carcinogenesis

Abstract: The tumorigenesis of neuroendocrine tumours remains poorly understood, although a minority, the familial multiple endocrine neoplasia (MEN 1 and MEN 2), are known to be of uncommon genetic origin. Mutation of the tumour suppressor gene, p53, is now known to be a common genetic alteration in about half of all types of non-endocrine cancers. In the present study, immunocytochemistry using the monoclonal anti-p53 antibody, DO-7, has been employed to investigate the accumulation of p53 immunoreactivity in a wide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 23 publications
6
17
0
Order By: Relevance
“…In contrast, we could not detect any abnormal immunostaining of p53 in five benign solitary phaeochromocytoma specimens without p53 gene mutations. These results agree with the report of Wang et al (1995) that showed no abnormal p53 immunostaining in 24 phaeochromocytoma specimens. The results of PCR-SSCP followed by direct DNA sequencing and immunohistochemistry demonstrated p53 gene mutations or intronic sequence alterations associated with abnormal accumulation of p53 protein phaeochromocytoma tissues from multiple and malignant cases.…”
Section: P53 Mutations In Adrenal Tumours · T Yoshimoto and Others 251supporting
confidence: 93%
“…In contrast, we could not detect any abnormal immunostaining of p53 in five benign solitary phaeochromocytoma specimens without p53 gene mutations. These results agree with the report of Wang et al (1995) that showed no abnormal p53 immunostaining in 24 phaeochromocytoma specimens. The results of PCR-SSCP followed by direct DNA sequencing and immunohistochemistry demonstrated p53 gene mutations or intronic sequence alterations associated with abnormal accumulation of p53 protein phaeochromocytoma tissues from multiple and malignant cases.…”
Section: P53 Mutations In Adrenal Tumours · T Yoshimoto and Others 251supporting
confidence: 93%
“…A rationale for such investigations comes from studies in mice with p53 mutations who develop PETs (Harvey et al 1995). Nevertheless, most studies found no mutations of P53 and/or no overexpression of the mutated protein in human PETs (Evers et al 1994, Wang et al 1995, Bartz et al 1996, Pavelic et al 1996, Moore et al 2001b. These data suggest that findings of LOH at 17q13 may be related to other unknown TSGs.…”
Section: Genetic Alterations Of Oncogenes and Tsgsmentioning
confidence: 94%
“…Studies have shown that overexpression of p53 in neuroendocrine tumors, including medullary carcinomas of the thyroid, is rare. 22,23 In contrast, it has been suggested that p53, which has been shown to be diffusely positive in three laryngeal moderately differentiated neuroendocrine carcinomas, may play a role in the pathogenesis of this tumor, unlike other neuroendocrine tumors. 5 However, these findings have not been validated.…”
Section: Ttf-mentioning
confidence: 94%